Association between central corneal thickness and systemic lupus erythematosus: a cross-sectional study protocol - Saldaña-Garrido, Juan David; Cantó-Cerdán, Mario; Gil-Guillén, Vicente Francisco; Alfaro-Beltrá, María Luisa; Sivera, Francisca (Frontiers in Medicine, 2024)
Introduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting multiple systems and classified under connective tissue disorders. Ocular involvement occurs in up to 30% of SLE cases, with the cornea being particularly susceptible to thinning due to immune-complex deposits and its predominantly type I collagen composition. This corneal thinning is clinically significant in glaucoma, where patients with reduced central corneal thickness (CCT) may have up to a threefold increased risk of developing glaucoma, as well as in refractive surgery. However, existing studies on CCT in SLE are limited and marked by substantial heterogeneity in methodology, technology, criteria, and participant numbers, resulting in conflicting findings. Based in our hypothesis that SLE-related corneal lysis may result in decreased CCT, this study aims to determine and compare the mean CCT values between SLE patients and healthy controls to obtain a more precise understanding of the potential relationship.A cross-sectional observational study will be conducted, enrolling SLE patients and age-and sex-matched healthy controls recruited from ophthalmology consultations. Exclusion criteria will be applied to rule out other corneal thinning risk factors. A pilot study estimated a minimum sample size of 34 participants per group. CCT measurements will be obtained using Zeiss HD Cirrus 5000 optical coherence tomography (OCT) on a randomly selected eye, following concordance analysis using the Kappa index. Statistical analysis will include descriptive, bivariate, and multivariate methods. The study protocol was approved by the ethics committee.Discussion: The cornea's vulnerability to thinning and lysis in SLE, which impacts CCT, is crucial for the accurate assessment of glaucoma, the leading cause of irreversible blindness worldwide and the second leading cause in Europe. Given that patients with reduced CCT are at a significantly higher risk of developing glaucoma, further research is necessary to understand the association between SLE and CCT. Our study aims to enhance methodological rigor compared to prior research by determining an appropriate sample size and exclusively enrolling SLE patients to increase participant homogeneity. If a significant difference in CCT between groups and an association between CCT and SLE are found, a prospective study will be considered.